EFEKTIVITAS PENGGUNAAN KARTU LADIES “LAWAN DISMENOREA” TERHADAP PENGETAHUAN REMAJA PUTRI tentang DISMENOREA - Ria Gustirini (IKesT Muhammadiyah Palembang, 2024)
Introduction :During menstruation, the problem experienced by most women is discomfort or severe pain. This is usually called menstrual pain (dysmenorrhea). There are still many women and even teenagers who consider menstrual pain to be normal, they assume it lasts 1-2 days. One effort to address the problem of lack of knowledge about dysmenorrhea is by providing health education through cards. This research aims to determine the effectiveness of using the ladies' card